(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Current research tries to identify the role of Lean Six Sigma in managing quality costs and increasing profitability in organizations through the application of quality cost approach utilizing target cost technique in order to influence management and reduction of quality costs and to improve competitive advantage. The concept of quality cost management is becoming the focus of many industrial and service organizations both in developed and developing economies, especially those concentrating on profitability improvement. This is due to that this approach is different in that it focuses on defining the rates of defective production and diagnosing malfunction areas in the production process. It also eliminates waste which is reflected in more reduction in quality costs. Consequently, the purpose of this research is to identify the applicability of this approach in the sampled factory by means of defining its contribution in reducing quality costs through the utilization of target cost approach. The research proves the applicability of this approach in the researched factory and its contribution to reducing quality costs and profitability improvement